Beyond Bollywood: the Cultural Politics of South Asian Diasporic Film. - Desai, Jigna (Taylor & Francis, 2004)
Beyond Bollywood is the first comprehensive look at the emergence, development, and significance of contemporary South Asian diasporic cinema. From a feminist and queer perspective, Jigna Desai explores the hybrid cinema of the 'Brown Atlantic' through a close look at films in English from and about South Asian diasporas in the United States, Canada, and Britain, including such popular films as My Beautiful Laundrette, Fire, Monsoon Wedding, and Bend it Like Beckham.
OCLC: 824549185
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé